The Happy Life: Nice Work if You Can Get It (Journal of the Association for the Study of Australian Literature, 2014)
Has any other writer so closely suggested that the aura of a work of art is a manifestation of joy? For David Malouf, happiness involves the complete immersion of a man or woman—he uses gender with all body parts intact—in moments of irreducible self-consciousness. In The Happy Life (2011), the Transcendentalist connections are clear, but Malouf’s is a thoroughly contemporary vision. As with Emerson and Thoreau, Malouf brings considerable Classical insight to modern problems of unhappiness, which he says generally spring from mistaking the material “good life” for the spiritual “happy life.” While acknowledging global problems of environment and politics, Malouf looks squarely at the possibilities for personal happiness in physical and intellectual self-awareness, moments that can be realized in the interstices and lapses of a world beyond individual control. The result is both a classical humanistic assertion of personal possibility and a modern registry of the odds against us.